1995
DOI: 10.1086/176210
|View full text |Cite
|
Sign up to set email alerts
|

Far-Infrared Spectral Observations of the Galaxy by COBE

Abstract: We derive Galactic continuum spectra from 5-96 cm −1 from COBE/FIRAS observations. The spectra are dominated by warm dust emission, which may be fit with a single temperature in the range 16-21 K (for ν 2 emissivity) along each line of sight. Dust heated by the attenuated radiation field in molecular clouds gives rise to intermediate temperature (10-14 K) emission in the inner Galaxy only. A widespread, very cold component (4-7 K) with optical depth that is spatially correlated with the warm component is also … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

31
219
1

Year Published

1996
1996
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 227 publications
(251 citation statements)
references
References 37 publications
31
219
1
Order By: Relevance
“…Structurally different dust grains, such as fluffy or fractal particles (Ossenkopf & Henning 1994;Paradis et al 2009) could produce the submillimeter excess. In fact, Reach et al (1995) propose this to be the explanation for the widespread cold dust component they found in the Milky Way from COBE/FIRAS measurements, after rejecting either very cold big dust grains or very small grains as a possibility. The dust grain emissivity β is not only a function of dust temperature, but it also depends on the grain composition.…”
Section: Possible Explanations For a Submillimeter Excessmentioning
confidence: 92%
See 1 more Smart Citation
“…Structurally different dust grains, such as fluffy or fractal particles (Ossenkopf & Henning 1994;Paradis et al 2009) could produce the submillimeter excess. In fact, Reach et al (1995) propose this to be the explanation for the widespread cold dust component they found in the Milky Way from COBE/FIRAS measurements, after rejecting either very cold big dust grains or very small grains as a possibility. The dust grain emissivity β is not only a function of dust temperature, but it also depends on the grain composition.…”
Section: Possible Explanations For a Submillimeter Excessmentioning
confidence: 92%
“…Thus, we cannot exclude in low-metallicity star-forming galaxies such as the LMC and the SMC the predominance of a dust grain population with different optical properties causing β to be around unity, or even the inconspicuous presence of such dust in more massive metalrich spiral galaxies (such as the Milky Way, cf. Reach et al 1995). However, it is not clear what this population is (but see Mény et al 2007), or what processes would lie at the root of its dominance in both star-forming dwarf galaxies and more extreme (ultra)luminous infrared galaxies, nor is it obvious that β could be as low as zero, as appears to be the case in the SMC.…”
Section: Possible Explanations For a Submillimeter Excessmentioning
confidence: 99%
“…Although the measured temperature difference between the regions is less strong than the luminosity increase, nevertheless, we see elevated temperatures in IRDC 18454 compared to IRDC 18223. Considering the large apertures used for the SEDs, the derived average temperatures may still be dominated by the average temperature of the general ISM that is in the same range (e.g., Reach et al 1995).…”
Section: Luminous Starless Clumpsmentioning
confidence: 99%
“…The presence of this cold dust component is still a contentious issue in the ISM community and will have important consequences on our comprehension of ISM properties of low metallicity environments. Lisenfeld et al (2001), Reach et al (1995), Dumke et al (2004), Bendo et al (2006) or Meny et al (2007) suggested that changes in dust emission properties (changes in dust emissivity or resonances related to dust impurities) should be responsible for boosting submm emission above the 15−20 K thermal emission expected at these wavelengths. However, not all low metallicity galaxies show submm excess, as shown recently by the observations of the nearby Local Group Galaxy IC 10 (Parkin et al 2009, in prep.…”
Section: Introductionmentioning
confidence: 99%